Peran Dana Desa Dalam Meningkatkan Pendapatan Masyarakat Ditinjau Dari Perspektif Ekonomi Islam : (Studi Kasus di Desa Bencah Kelubi Kec. Tapung Kab. Kampar) - Haryono, Edi; Siregar, Nisa Anggraini (EL-EMIR Institute, 2024)
This research is qualitative research with the main aim to describe or describe in detail and in depth the process of implementing village funds so that they can provide a role/contribution as expected by the central government. The technique used in this research is a qualitative descriptive technique. Qualitative descriptive means collecting existing data, then interpreting and describing the data relating to the situation that is occurring and then connecting it to the problem that is occurring. From the research results, the processing of village funds in Bencah Kelubi Village, Tapung District, Kampar Regency was carried out based on existing technical instructions so that community empowerment from 2015 to 2017 began to increase in terms of development, but there was still minimal improvement in community economic empowerment. The policies implemented by the government in carrying out its duties are benchmarked against the basic values ​​of Islamic economics, namely: ownership, balance and justice. The government collaborates with institutions in the village, and the decisions taken by the government are joint decisions in the Village Development Plan Deliberation (Musrenbangdes).